Pengaruh Moticasi Ekstrinsik dan Lingkungan Kerja Terhadap Kinerja Karyawan Dengan Disiplin Kerja Sebagai Variabel Mediasi - Dinny Febriani (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to see the effect of motivation and work environment on employee performance with work discipline as a mediating variable for the employees of the Bagelen District Office. The population for this study were employees of the Bagelen District Office, Purworejo Regency. The sample used was 45 respondents. The technique used in this research is saturated sampling. The data analysis technique used the SPSS 25 application. This study used a quantitative approach. The test instruments used in the study were validity and reliability tests. The data analysis technique used in this research is descriptive analysis, classical assumption test, normality test, multicolinearity test, heteroscedasticity test. The hypothesis test used in this study is the t test. The results showed that extrinsic motivation has a positive effect on employee performance, the work environment has a positive effect on employee performance, work discipline has a positive effect on employee performance, extrinsic motivation has a positive effect on employee performance through work discipline, the work environment has a positive effect on employee performance through work discipline. Keywords: Extrinsic Motivation, Work Environment, Work Discipline, Employee Performance.